Can CuFeS2 be used in a sensitized thermal cell?. (September 2020) - Sekiya, H.; Isobe, T.; Nakajima, A.; Matsushita, S.
Abstract: Sensitized thermal cell (STC) is a new method for converting heat directly into electric power; STC mimics a dye-sensitized solar cell. Up to now, the power generation by STC has been reported for β-FeSi2, Ge, and Ag2 S; however, these materials are relatively expensive. In this study, CuFeS2, which is abundant on the Earth, was examined as the STC material. Graphical abstract: Image 1 Highlights: CuFeS2 was examined as the sensitizer of STC. Electric power generation was observed. A highly pure CuFeS2 semiconductor will improve the output power.